Flexible woven metal wires supported nanosheets and nanoparticles double-layered nitrogen-doped zinc stannate toward enhanced solar energy utilization. Issue 1 (January 2018) - Li, Zhengdao; Ma, Qinge; Li, Yuling; Liu, Ruiheng; Yang, Hao
Abstract: For enhanced solar energy application, double-layered nitrogen-doped Zn2 SnO4 film consisting of bottom nanosheets and top nanoparticles is designed and synthesized on flexible woven metal wires. The effects of doping concentration of nitrogen element (N) and the amount of coating nanoparticles on electronic, optical properties and stability are investigated in detail by various testing techniques. The results show that in the double-layered structure, the nanosheets array can provide direct transport pathways for photoinduced electrons, while the nanoparticles can provide high surface area. On the other hand, doped N element is conducive not only to the absorption of visible light due to narrowed band gap, but also to suppression of charge recombination. With the optimized double-layered N-doped Zn2 SnO4 as photoanodes of flexible dye-sensitized solar cells, the corresponding photoelectric conversion efficiency is 2.302% compared to 1.332% and 1.826% in case of pure Zn2 SnO4 nanosheets and N-doped Zn2 SnO4 nanosheets; The double-layered N-doped Zn2 SnO4 is also determined to be high-performance immobilized photocatalyst with a better recyclability for the photodegradation of organic pollutant under sunlight irradiation; More importantly, the preparation methods is also applicable to fabricate other composite oxides on wire-shaped substrate for more practical applications in flexible devices.